Enhancement of Secondary Cell Wall Formation in Poplar Xylem Using a Self-Reinforced System of Secondary Cell Wall-Related Transcription Factors - Nakano, Yoshimi; Endo, Hitoshi; Gerber, Lorenz; Hori, Chiaki; Ihara, Ayumi; Sekimoto, Masayo; Matsumoto, Tomoko; Kikuchi, Jun; Ohtani, Misato; Demura, Taku (Frontiers in Plant Science, 2022)
The secondary cell wall (SCW) in the xylem is one of the largest sink organs of carbon in woody plants, and is considered a promising sustainable bioresource for biofuels and biomaterials. To enhance SCW formation in poplar (Populus sp.) xylem, we developed a self-reinforced system of SCW-related transcription factors from Arabidopsis thaliana, involving VASCULAR-RELATED NAC-DOMAIN7 (VND7), SECONDARY WALL-ASSOCIATED NAC-DOMAIN PROTEIN 1/NAC SECONDARY WALL THICKENING-PROMOTING FACTOR3 (SND1/NST3), and MYB46. In this system, these transcription factors were fused with the transactivation domain VP16 and expressed under the control of the Populus trichocarpa CesA18 (PtCesA18) gene promoter, creating the chimeric genes PtCesA18pro::AtVND7:VP16, PtCesA18pro::AtSND1:VP16, and PtCesA18pro::AtMYB46:VP16. The PtCesA18 promoter is active in tissues generating SCWs, and can be regulated by AtVND7, AtSND1, and AtMYB46; thus, the expression levels of PtCesA18pro::AtVND7:VP16, PtCesA18pro::AtSND1:VP16, and PtCesA18pro::AtMYB46:VP16 are expected to be boosted in SCW-generating tissues. In the transgenic hybrid aspens (Populus tremula × tremuloides T89) expressing PtCesA18pro::AtSND1:VP16 or PtCesA18pro::AtMYB46:VP16 grown in sterile half-strength Murashige and Skoog growth medium, SCW thickening was significantly enhanced in the secondary xylem cells, while the PtCesA18pro::AtVND7:VP16 plants showed stunted xylem formation, possibly because of the enhanced programmed cell death in the xylem regions. After acclimation, the transgenic plants were transferred from the sterile growth medium to pots of soil in the greenhouse, where only the PtCesA18pro::AtMYB46:VP16 aspens survived. A nuclear magnetic resonance footprinting cell wall analysis and enzymatic saccharification analysis demonstrated that PtCesA18pro::AtMYB46:VP16 influences cell wall properties such as the ratio of syringyl (S) and guaiacyl (G) units of lignin, the abundance of the lignin β-aryl ether and resinol bonds, and hemicellulose acetylation levels. Together, these data indicate that we have created a self-reinforced system using SCW-related transcription factors to enhance SCW accumulation.